Physics learning, technology integration, and students' epistemological beliefs in a constructivist learning environment - Pabellon, Josefina Llarena (Animo Repository, 2005)
Personal epistemological beliefs are a persons views about the nature of knowledge and learning beliefs about how individuals come to know and how knowledge is constructed. The growing evidence in the literature indicates that epistemological beliefs influence student learning. This study investigated how course structure impacts on students epistemological beliefs. The context of the study was a redesigned course in optics with features intended to create a constructivist learning environment and with curricular elements focused on the development of epistemological beliefs. In classroom transactions, the active learning mode was used instead of the lecture mode. Technology was integrated for students to learn optics with. The redesigned course structure included features that aimed to make students aware of how they learn the concepts and the nature of the knowledge they are learning. The course was taught by the researcher during the second semester of academic year 2003 -2004. The class consisted of 23 students in the Bachelors of Secondary Education major in physics (BSE Physics) program. With respect to optics, this study found that successful learning is accompanied by the development of more sophisticated epistemological beliefs. Instructional practices and curricular elements explicitly intended to foster epistemological development can lead to significant improvement in students views about knowledge and learning as evidenced by the significant pre-post gains in students scores in an epistemological belief survey instrument. Students scores in two epistemological belief survey questionnaires used in the study were found to correlate positively (p < 0.05) with the students final grade in the course and with their post test scores in a test on conceptual understanding of basic concepts in optics. Since epistemological expertise correlates positively with academic performance, it can be reasonably inferred that a sophisticated epistemological stance supports productive study habits and metacognitive practices. Students learn more successfully when they understand physics knowledge as a coherent system of ideas, the formalism as a means for expressing and working with those ideas, and the task of learning as a matter of reconstructing and refining ones current understanding.